Problem with integral conditions in the time variable for Sobolevtype system of equations with constant coefficients - Kuz, A. M.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
In a domain obtained as a Cartesian product of an interval $[0, T]$ and the space $R^p, p \in N$, for a system of equations (withconstant coefficients) unsolved with respect to the highest time derivative, we study a problem with integral conditions inthe time variable in the class of functions almost periodic in the space variables. A criterion of uniqueness and sufficientconditions for the existence of the solution of this problem in different functional spaces are established. We use the metricapproach to solve the problem of small denominators encountered in the construction of the solution.